Therapeutic Challenges of Diabetes Mellitus-Related Erectile Dysfunction and The Potential Therapeutic Role of Medicinal Plants: A Narrative Review - Wang H; Chang H; Sun D; Wang A; Yan B; Chung E (Drug Design, Development and Therapy)
Hao Wang,1 Hongyuan Chang,1 Di Sun,1 Anmin Wang,1 Bin Yan,1 Eric Chung2,3 1Department of Andrology, Xiyuan Hospital of China Academy of Chinese Medical Sciences, Beijing, People’s Republic of China; 2Department of Urology, Princess Alexandra Hospital, University of Queensland, Brisbane, QLD, Australia; 3AndroUrology Centre, Brisbane, QLD, AustraliaCorrespondence: Bin Yan, Department of Andrology, Xiyuan Hospital of China Academy of Chinese Medical Sciences, Beijing, 100091, People’s Republic of China, Email yanbinxyyy@126.com Eric Chung, Department of Urology, Princess Alexandra Hospital, University of Queensland, Brisbane, QLD, 4102, Australia, Email ericchg@hotmail.comAbstract: Erectile dysfunction (ED) is a common male sexual dysfunction and can be induced by diabetes mellitus (DM). Diabetes mellitus-induced erectile dysfunction (DMED) affects various aspects of the patient’s quality of life, mental well-being, and relationship dynamics. Given the increasing incidence of DM worldwide, the incidence of DMED is expected to increase accordingly. There are more challenges to treat DMED compared to non-DMED. The efficacy of oral phosphodiesterase-5 inhibitors is often ineffective in DMED and there is a need to search for effective drugs. Medicinal plants such as Eucommia ulmoides Oliv. Leaf, Cordycep militaris have been used in treating DMED in some experiments. And some ingredients from the medicinal plants such as Icariside II, Panax notoginseng Saponins have also shown to be beneficial in improving erectile function in animal models of DMED. These medicinal plants and ingredients may act by regulating hormone levels, ameliorating oxidative damage, and promoting NO/cGMP. We summarize the challenges in treating DMED due to related complicated pathogenesis and limited therapeutic options, while particularly highlight the role of the medicinal plants and their ingredients in DMED.Keywords: erectile dysfunction, diabetes mellitus, medicinal plant, mechanism, treatment